Analisis Semiotik Kebun Binatang Dalam Photobook Berjudul Wildtopia - Radityo Widiatmojo (Sospol : Jurnal Sosial Politik, 2018)
This research conducts an attempt to extend the meaning of zoo in society by Sander Pierce's semiotica analysis on Photobook titled Wildtopia. By qualitative method, this research finds that the zoo have a dualism function in a very contrast way. In one hand, the zoo gives a representational experience as objectivate the animal for human knowledge. On the other hand, zoo it self destruct the wildness of each animal as they are taking care by human. Another interesting finding shows photography is able to criticized phenomenon in society as a visual argument.